2009
DOI: 10.1002/clen.200900160
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Process in Soil Surface Containing Calcic Nodules on the Northern Loess Plateau of China by Simulated Experiments

Abstract: Soil containing calcic nodules is widely present on the northern Loess Plateau of China owing to soil genesis under local climate conditions. In most studies, little attention is payed to the effect of calcic nodules on soil evaporation and ecoenvironment, resulting in inaccurate evaporation estimation in this kind of soil and further improper field water management measures and irrigation effects. In this paper, soil column experiments were conducted in order to investigate evaporation process in soil contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Zhou et al [41] reported that the infiltration rate and saturated hydraulic conductivity of soil moisture decreased with the increasing gangue content. Moreover, another study indicated that soil evaporation reduction was positively related to the calcic nodule content in a Chinese Loess Plateau soil [42]. In karst depression area, soil surface and topsoil are often characterized by the presence of rock.…”
Section: Influencing Factors Of Soil Moisture Variabilitymentioning
confidence: 98%
“…Zhou et al [41] reported that the infiltration rate and saturated hydraulic conductivity of soil moisture decreased with the increasing gangue content. Moreover, another study indicated that soil evaporation reduction was positively related to the calcic nodule content in a Chinese Loess Plateau soil [42]. In karst depression area, soil surface and topsoil are often characterized by the presence of rock.…”
Section: Influencing Factors Of Soil Moisture Variabilitymentioning
confidence: 98%
“…Additionally, Yang et al (2014) reported that soil water decreases drastically after vegetation restoration, with no significant difference in near-surface soil moisture among the vegetation types but significant differences in the sub-surface and deep soil layers. Previous studies have mainly focused on soil water in the shallow layers, whereas soil water in deeper layers has largely been ignored due to the high costs of labor and time required for such investigation (Gao and Shao, 2012;Tombul, 2007;Wang et al, 2013;Zhu et al, 2009;Zhu, 2014. Therefore, water resources in deep soil profiles play an important role in ensuring a well-established vegetation cover in semi-arid regions, and understanding the response of deep soil water to vegetation restoration is essential for estimating the productivity and sustainability of semi-arid ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolving and leaching of CaCO 3 by rainwater, followed by the evaporation and rapid removal of soil water by plants, leads to CaCO 3 precipitation and the development of caliche deposits in soils and formation of caliche nodules . Caliche nodules can change the soil structure and hydrologic processes (i.e., evaporation and infiltration) due to their diameter and the water absorption of different soil particles . Some studies have found that soil evaporation and infiltration both decrease with an increase in caliche nodule content (CNC), which could be partly attributed to water absorption by caliche nodules and water distribution between the soil and the caliche nodules .…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43] Caliche nodules can change the soil structure and hydrologic processes (i.e., evaporation and infiltration) due to their diameter and the water absorption of different soil particles. [39,[44][45][46][47] Some studies have found that soil evaporation and infiltration both decrease with an increase in caliche nodule content (CNC), which could be partly attributed to water absorption by caliche nodules and water distribution between the soil and the caliche nodules. [46,47] Caliche nodules may also restrict downward water movement due to the formation of calcareous crusts in the deep soil layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation